PERANCANGAN SISTEM INFORMASI GEOGRAFIS PERTANIAN DAN PERKEBUNAN DI KABUPATEN MUARA ENIM BERBASIS WEB - Baibul Tujni (Jurnal Informatika Global)
One computer-based technology to support agriculture and plantation area planning is a Geographic Information System (GIS) where the system is able to create a model which gives an overview, description and estimate of a factual conditions. Geographical potential of a region is very important for the development of the region, there are several potential areas, namely agriculture, and plantation, This potential will grow annually in accordance with the development on the local area, with the development of this region will generate the competitiveness of each respective region / areas in order to support the realization of development. Potential agricultural areas and plantation Muara Enim district will develop well managed properly, so it will contribute to regional economic revenue increases. To be able to know information comparison Muara Enim regency administration area required a geographic information system to determine the spread of plantations and agricultural potential that can be realized through the technology of web-based geographic information system.Keyword: Information Systems Geogrfis, plantation and agriculture, ArcGIS